A descriptive study of the common denture cleaning practices of UPCD prosthodontic patients from the year 1990-1996 - King, Ann Francis
It is generally recognized that unclean dentures may have undesirable effect on patients' oral health and ability to successfully wear dentures. A survey on denture cleaning method was carried out on U.P.C.D. denture patients who visited the Prosthodontic Section from the year 1990-1996. A total of 100 subjects were asked to complete a questionnaire, 66 of which were complete denture wearers and 44 were removable partial denture wearers. The study aimed to compare the denture cleaning methods of the subjects to the most widely accepted way of denture cleaning which is the combined treatment of brushing with an abrasive paste and soaking in a denture cleaner. Results show 75.5 % of the subjects use toothbrush with toothpaste, 14.5% use toothbrush with detergent, 8.2% soak dentures impure water, and 1.8% soak in denture cleanser or use toothpaste with denture paste. Therefore, the cleaning practices of the U.P.C.D. prosthodontic patients are significantly different from the most accepted denture cleaning method.